Mental health as perceived by Norwegian adolescents living with parental somatic illness: Living in an earthquake zone. Issue 1 (1st January 2020) - Eide, Torill; Faugli, Anne; Kufås, Elin; Mjøsund, Nina Helen; Eilertsen, Grethe
ABSTRACT: Purpose: Severe parental somatic illnesses can influence the entire family, including adolescents' everyday life, psychosocial functioning and health. Within salutogenesis, it is highlighted that stressor life events, such as parental somatic illness, might lead to a chain of events that can produce tension. There is a lack of in-depth understanding regarding how adolescents living in a situation with a severely somatically ill parent (SIP) perceive their own mental health. The aim of this study was therefore to explore the lived experience of Norwegian adolescents living with an SIP, and their perception of the parental illness' influence on their mental health. Methods: Interpretative phenomenological analysis was used. In-depth interviews were conducted with 11 adolescents (aged 13–18 years) who had an SIP. Two adolescents with an SIP participated in study preparation and data analysis. Results: Adolescents perceived parental somatic illness as a multifaceted influence on their mental health as it represented both personal and relational strain and growth. Their perceptions can be conceptualized by the super-ordinate theme "living in an earthquake zone", and by two themes, "inner shakes—but not falling apart" and "relational aftershocks—gains and losses". Conclusion: For adolescents, parental somatic illness means personal and relational strain and growth.